2017
DOI: 10.1152/ajpcell.00291.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sarcolipin deletion on skeletal muscle adaptive responses to functional overload and unload

Abstract: Overexpression of sarcolipin (SLN), a regulator of sarco(endo)plasmic reticulum Ca-ATPases (SERCAs), stimulates calcineurin signaling to enhance skeletal muscle oxidative capacity. Some studies have shown that calcineurin may also control skeletal muscle mass and remodeling in response to functional overload and unload stimuli by increasing myofiber size and the proportion of slow fibers. To examine whether SLN might mediate these adaptive responses, we performed soleus and gastrocnemius tenotomy in wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 62 publications
(90 reference statements)
6
35
2
Order By: Relevance
“…Horse SR shows ~2-fold greater Ca 2+ transport than rabbit SR, in spite of a ~2-fold lower SERCA content. These results are consistent with transgenic mouse models, where knock-out of SLN increases SERCA activity and overexpression of SLN decreases SERCA activity (35,36,145). The 2-fold greater Ca 2+ load and higher CASQ expression in horse SR vesicles suggest that horse myocytes may be able to store and release more intracellular Ca 2+ than rabbit myocytes.…”
Section: Physiological Implications Of Null-sln and Supra-csq Expresssupporting
confidence: 84%
“…Horse SR shows ~2-fold greater Ca 2+ transport than rabbit SR, in spite of a ~2-fold lower SERCA content. These results are consistent with transgenic mouse models, where knock-out of SLN increases SERCA activity and overexpression of SLN decreases SERCA activity (35,36,145). The 2-fold greater Ca 2+ load and higher CASQ expression in horse SR vesicles suggest that horse myocytes may be able to store and release more intracellular Ca 2+ than rabbit myocytes.…”
Section: Physiological Implications Of Null-sln and Supra-csq Expresssupporting
confidence: 84%
“…The left ventricle was used to examine SERCA protection by PLN for the same reason. We suggest in mice, SLN and PLN would be expected to protect SERCA in slow-twitch muscle where they are normally expressed [62][63][64][65] but not in fast-twitch muscle where they are not normally expressed [64,66]. However, in humans, SLN would be expected to provide greater SERCA protection in fast-twitch muscle, which contains relatively high levels of SLN and relatively low levels of PLN protein, whereas PLN would be expected to provide greater SERCA protection in slow-twitch muscle, which contains relatively high levels of PLN and relatively low or undetectable levels of SLN protein [65].…”
Section: Discussionmentioning
confidence: 93%
“…SLN but not PLN increases the amount of energy required by SERCA pumps, making SLN a key modulator of skeletal muscle energy metabolism, and it is protective against diet-induced obesity (for review see [83,84]). In a series of recent studies, we have also discovered that SLN plays a critical role in activating calcium signaling pathways that control adaptations in muscle mass and fiber type under conditions of muscle overload, disuse and disease [64,85,86]…”
Section: Discussionmentioning
confidence: 99%
“…Although both groups had comparable height and lean mass in the upper extremities, the overweight subjects had ~10% greater lean mass in the lower extremities reflecting an increased mechanical loading due to their excessive body mass. Even though functional overloading has been associated with increased SLN expression in mice, no significant differences in vastus lateralis SLN protein expression were observed between the overweight and lean subjects. A potential explanation for this finding could be that much larger overloading may be required to increase SLN expression in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with rodent data, here we have demonstrated that a short training program based on repeated high‐intensity exercise reduced the SLN protein levels in vastus lateralis despite eliciting much less total energy expenditure than the 4‐day walking intervention. A principal difference between prolonged walking and repeated 30‐second all‐out sprints is the marked metabolic disturbances evoked by the sprints, which cause substantial lactic acidosis, oxidative stress, and sarcoplasmic reticulum stress .…”
Section: Discussionmentioning
confidence: 99%